Pengaruh Model Pembelajaran Project Based Learning Terhadap Hasil Belajar Kognitif Siswa Pada Mata Pelajaran Pendidikan Agama Islam - Maria, Anly; Maulana, Risma (MASAGI : Jurnal Pendidikan Agama Islam, 2023)
Cognitive learning outcomes are essential in the educational process as they stimulate students to learn. However, cognitive learning outcomes in Islamic Religious Education (PAI) subjects have been notably low. This is evidenced by mid-term test (UTS) results that have not met the minimum competency standards (KKM), and a significant number of students still struggle to understand the material, indicating a need for optimization in cognitive learning outcomes. The project-based learning model (PBL) has been selected for the PAI subject as a means to improve students' learning outcomes and encourage independent, creative, and innovative learning. This study aims to describe the impact of the project-based learning model on the cognitive learning outcomes of students in the Islamic Religious Education subject for Grade XI IPS 2 at SMAN 19 Bayongbong Garut. The research employs a quantitative descriptive correlational method. Data collection techniques include observation, questionnaires, interviews, and document analysis, with data processing carried out through statistical analysis. The findings indicate that the implementation of the project-based learning model in the PAI subject scored an average of 4.44, placing it within the 4.01 – 5.00 interval, which is categorized as excellent. The improvement in students' cognitive learning outcomes in PAI subjects also averaged 4.03, within the same interval of 4.01 – 5.00, indicating a very good category. Based on statistical testing using simple regression analysis, project-based learning was found to influence cognitive learning outcomes by 60.10%, aligning with the functions and objectives of Islamic Religious Education. The remaining 30.90% is influenced by other factors not covered in this study.  Keywords : Project-Based Learning Model, Cognitive Learning Outcomes, Islamic Religious Education.